Relationship between study habits and achievements of grade ten students in Nepal - Poudel, Tek Narayan (Journal of Advanced Academic Research, 2017)
The study environment can have a big effect on the overall performance of students. Factors such as noise, interruptions, lighting, temperature, neatness, comfort and equipment can play a major role in shaping the performance of the student. Study habit involves different kinds of personality traits, attitudes, thinking processes, and behaviors related to how a person approaches a learning task. Improving study skills likely involves changing some habits, and making a conscious decision to do so. It is essential to assess the current study habits and its effect on the achievement of students. The study was conducted among the 511 grade ten students of three districts of Nepal. It shows very weak effect of study habit on performance of student. Regression analysis between the study habit and achievement shows that study habit could explain only 2%-8% variation on achievement of students so it indicates the need of improvement in study habit. Proper orientation of study habit is not adequate among the management, teacher, guardians and students so it should be taken serious by concerned person to improve the effectiveness of study habit.  Journal of Advanced Academic Research Vol. 3, No.3, 2016, page:40-52